Association of aquaporin-4 antibody-seropositive optic neuritis with vision-related quality of life and depression - Song, Ruitong; Huang, Wenqiao; Yang, Jun; Tang, Xueshan; Huang, Yihua; Chen, Yingying; Zhao, Mukun; Hu, Qiuming; Du, Yi (Frontiers in Neurology, 2023)
Objective Aquaporin-4 (AQP4) antibody-seropositive optic neuritis (AQP4-ON) is one of the most common types of optic neuritis in China. However, the association between AQP4-ON and vision-related quality of life (QoL) and depression remains poorly understood. Methods In this cross-sectional study, 57 patients with optic neuritis were evaluated for their vision-related QoL using a Chinese version of the 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) and assessed for depressive symptoms using a Chinese version of the Beck Depression Inventory-II (BDI-II). Data regarding participants’ age, sex, visual acuity, and the number of recurrence events were gathered. Linear regression analysis was employed to investigate the relationships between AQP4-ON and vision-related QoL, as well as depression. Results Of the 57 included patients, 28 were AQP4-ON, and 29 were idiopathic optic neuritis (ION). AQP4-ON demonstrated a significant correlation with a decreased VFQ-25 composite score (Mean difference, −11.65 [95% CI, −21.61 to −1.69]; p = 0.023) and an increased BDI-II score (Mean difference, 6.48 [95% CI, 0.25 to 12.71]; p = 0.042) when compared to ION. The BDI-II score was correlated with the VFQ-25 composite score (Spearman ρ = −0.469; p < 0.001) but not with the visual acuity in the worse-seeing eye (Spearman ρ = 0.024; p = 0.860) or in the better-seeing eye (Spearman ρ = −0.039; p = 0.775), bilateral severe visual impairment (Spearman ρ = 0.039; p = 0.772) or the number of recurrence events (Spearman ρ = 0.184; p = 0.171). Conclusion AQP4-positive optic neuritis is associated with a decline in vision-related quality of life as well as an increased likelihood of experiencing depression. It is crucial for clinicians to assess both vision-related QoL and depression in patients with AQP4-positive optic neuritis to provide patient-centered care.